Proceedings of the 26th ACM SIGSPATIAL International Conference on Advances in Geographic Information Systems 2018
DOI: 10.1145/3274895.3274902
|View full text |Cite
|
Sign up to set email alerts
|

Stella

Abstract: Geotagged data (e.g. images or news items) have empowered various important applications, e.g., search engines and news agencies. However, the lack of available geotagged data significantly reduces the impact of such applications. Meanwhile, existing geotagging approaches rely on the existence of prior knowledge, e.g., accurate training dataset for machine learning techniques. This paper presents Stella; a crowdsourcing framework for image geotagging. The high accuracy of Stella is resulted by being able to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…While online crowdsourcing markets make it convenient to pay for workers willing to solve a range of diferent tasks, they suffer from limitations such as not attracting enough workers with desired background or skills [4,21,54]. For example, it can be a challenge to recruit workers for a task that requires workers who speak a specifc language or who live in a certain city [10,42] . Situated crowdsourcing can help fll in the gaps in these scenarios where the crowd needs to be associated with some context.…”
Section: Related Work 21 Situated Crowdsourcingmentioning
confidence: 99%
See 2 more Smart Citations
“…While online crowdsourcing markets make it convenient to pay for workers willing to solve a range of diferent tasks, they suffer from limitations such as not attracting enough workers with desired background or skills [4,21,54]. For example, it can be a challenge to recruit workers for a task that requires workers who speak a specifc language or who live in a certain city [10,42] . Situated crowdsourcing can help fll in the gaps in these scenarios where the crowd needs to be associated with some context.…”
Section: Related Work 21 Situated Crowdsourcingmentioning
confidence: 99%
“…It allows for a geo-fenced and more contextually controlled crowdsourcing environment, thus enabling targeting certain individuals, leveraging people's local knowledge or cognitive states, or simply reaching an untapped source of potential workers [27][28][29]34]. Researchers have discussed benefts of targeting geographically or temporally situated crowds over generic crowds in scenarios like providing emergency services in disasters [56], geotagging photos [42], etc. An experiment by Ipeirotis et al automatically identifed "situated crowds" with desired competence to complete a task and demonstrated that the cost of hiring workers through their platform is less than that of hiring workers through paid crowdsourcing platforms [38].…”
Section: Related Work 21 Situated Crowdsourcingmentioning
confidence: 99%
See 1 more Smart Citation